The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1093/ps/76.11.1474
|View full text |Cite
|
Sign up to set email alerts
|

Drinking water contaminants (arsenic, cadmium, lead, benzene, and trichloroethylene). 1. Interaction of contaminants with nutritional status on general performance and immune function in broiler chickens

Abstract: The objective of this study was to examine possible interactions between drinking water contaminants and suboptimal nutritional status for performance and immune function in male broiler chickens. Experimental drinking water contained a mixture of arsenic, benzene, cadmium, lead, and trichloroethylene (TCE) at low concentrations (0.80, 1.3, 5.0, 6.7, and 0.65 ppm) and high concentrations (8.6, 13, 50, 67, and 6.5 ppm). These chemicals were selected because they are among the most common contaminants found in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 40 publications
2
43
0
Order By: Relevance
“…Decreased feed intake and weight gain have also been previously reported in other models, i.e. broilers, and fish (Vodela et al 1997;Pedlar et al 2002). In addition to changes in food intake/weight gain, emaciation and lacrimation in arsenicexposed Mallard ducklings has been documented (Hoffman et al 1992).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Decreased feed intake and weight gain have also been previously reported in other models, i.e. broilers, and fish (Vodela et al 1997;Pedlar et al 2002). In addition to changes in food intake/weight gain, emaciation and lacrimation in arsenicexposed Mallard ducklings has been documented (Hoffman et al 1992).…”
Section: Discussionmentioning
confidence: 57%
“…recall that tuberculin injection occurred at Day 32 of age). Still, the increases in phagocytic activity were somewhat unexpected in that other studies with various host species reported that phagocytic activity of isolated macrophages/cells in situ were significantly decreased by arsenic exposure (Vodela et al 1997;Nayak et al 2007;Aggarwal et al 2008;Das et al 2010).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In this regard, only 2.8% of water on earth is fresh water; therefore, groundwater resources are highly valued due to their certain properties such as wide-spread occurrence and availability, and also good quality as an ideal supply of drinking water; due to these reasons more than half of the world's population depend on groundwater for survival (1)(2)(3)(4)(5)(6)(7). During the last few decades, contamination of groundwater resources is among the most important environmental issues due to hazardous chemical compounds such as heavy metals, pesticides, and petroleum hydrocarbons (8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%